2002
DOI: 10.1021/ma011530y
|View full text |Cite
|
Sign up to set email alerts
|

Miscibility and Phase Structure of Blends of Poly(ethylene oxide) with Poly(3-hydroxybutyrate), Poly(3-hydroxypropionate), and Their Copolymers

Abstract: The miscibility and phase behavior of poly(ethylene oxide) (PEO) blends with poly(3hydroxybutyrate) (P(3HB)), poly(3-hydroxypropionate) (P(3HP)), and poly(3-hydroxybutyrate-co-3-hydroxypropionate)s (P(3HB-co-3HP)s) have been investigated by differential scanning calorimetry (DSC) and high-resolution solid-state 13 C nuclear magnetic resonance (NMR). Four bacterial P(3HB-co-3HP) samples with 3HP contents of 15, 25, 46, and 76 mol % have been used in order to investigate possible influence of the sequence struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Blending of PHB with another kind of polymer may improve its properties and processability. PHB has been reported to be miscible with a few chemically synthesized polymers, such as poly(ethylene oxide)(PEO) [4][5][6][7][8][9][10]. PEO is semi-crystalline, biocompatible, biodegradable, non-ionic and water-soluble polymer of considerable industrial significance which finds applications in many different branches of industry [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blending of PHB with another kind of polymer may improve its properties and processability. PHB has been reported to be miscible with a few chemically synthesized polymers, such as poly(ethylene oxide)(PEO) [4][5][6][7][8][9][10]. PEO is semi-crystalline, biocompatible, biodegradable, non-ionic and water-soluble polymer of considerable industrial significance which finds applications in many different branches of industry [11].…”
Section: Introductionmentioning
confidence: 99%
“…PEO is semi-crystalline, biocompatible, biodegradable, non-ionic and water-soluble polymer of considerable industrial significance which finds applications in many different branches of industry [11]. Blending PHB with PEO was expected to give practical products that might be applied in biomedical materials and other fields [9]. Hence, miscibility, mechanical, optical, morphological and thermal properties of PHB/PEO blends has already been studied in the literature [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The melting temperature is lowest in poly(3HP-co-3HB)s with 3HP content of between 50 and 80 mol%. In the same range of content, fusion enthalpy is also lowest (19,20,38,43,56 (Fig. 2).…”
Section: Chemical and Physical Propertiesmentioning
confidence: 78%
“…We now focus on the impact of various levels of 3HP content on chemical and physical characteristics with regard to industrial applications. The T g decreases linearly with increasing 3HP moieties (16,20,43,56). The melting temperature is lowest in poly(3HP-co-3HB)s with 3HP content of between 50 and 80 mol%.…”
Section: Chemical and Physical Propertiesmentioning
confidence: 96%
“…[25] The PEO (M v ¼ 3.0 Â 10 5 g Á mol À1 ) was found to be miscible with bacterial P(3HB), chemosynthesized P(3HP) and bacterial poly(3-hydroxybutyrate-co-3-hydroxypropionate) [P(3HB-co-3HP)] copolymers in the amorphous phase over the whole blend composition range. [26] The miscibility of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) [P(3HB-co-3HV)] with PEO (M w ¼ 1.0 Â 10 5 g Á mol À1 ) was also investigated and they were found to be miscible in molten state, at least in the marginal composition ranges, where one of the components was in excess. [27] The miscibility of P(3HB-co-3HHx)/PEG and P(3HB-co3HHx)/methoxy poly(ethylene glycol) (MPEG) has been reported by Lim et al [28] Both the blend systems were found to be miscible in the melt state.…”
Section: Introductionmentioning
confidence: 99%